2000
DOI: 10.1080/10942910009524628
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of concentrated yogurt (Labneh)

Abstract: In this paper, the rheological behavior of concentrated yogurt (Labneh) is presented. The rheological behavior of Labneh was measured using a rotational viscometer in a temperature range of 5-55°C. The tested Labneh exhibited shear-thinning and thixotropic behaviors. The power law model expressed as τ = mγ n was found to be the most appropriate for the rheological model of Labneh. The effects of temperature on power law parameters were determined. The parameter (m) significantly decreased with increasing tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
4
14
0
Order By: Relevance
“…Storage time had a negligible effect on flow properties of destructured labneh. Similar observation was reported by Abu‐Jdayil et al . (2000).…”
Section: Miscellaneous Propertiessupporting
confidence: 92%
“…Storage time had a negligible effect on flow properties of destructured labneh. Similar observation was reported by Abu‐Jdayil et al . (2000).…”
Section: Miscellaneous Propertiessupporting
confidence: 92%
“…An addition of fat resulted in an overall increased compactness of the gel yoghurt microstructure (Krzeminski et al, 2011). Shaker et al (2000) found that the increase in fat content of plain yoghurt led to an increase in viscosity. In addition, the rate of the structure is slower than the breakdown rate.…”
Section: Resultsmentioning
confidence: 99%
“…For a shear thinning material follows the power law model like yoghurt (Benezech and Maingonnat 1993;Abu-Jdayil et al, 2000;Abu-Jdayil, 2003;Aportela-Palacios et al, 2005;Renan et al, 2009), and by taking the order of the structure breakdown "p" equals two for stirred yoghurt (Benzech and Maingonnat, 1993), then the structural decay parameter, m, can be given by:…”
Section: Methodsmentioning
confidence: 99%
“…Two variables that affect rheological properties of adhesive are the temperature and concentration of borax. The rheological properties of various materials such as labneh from barine milk, soups, cooked cassava and cassava starch with borax blends have been extensively studied by research groups [7] [11] [12]. However, literature does not provide adequate information for the rheological characterization of yam and potato borax blends for adhesive purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable rheological data are essential for design, quality control, sensory assessment, stability and consumer acceptance of a particular product [12]- [14]. It is also required for process engineering analysis (pumping, mixing, agitation, heating, shelf-life estimation, texture evaluation, product development and the development constitutive equation for rheological characterization [15]).…”
Section: Introductionmentioning
confidence: 99%